Fabrication of Miniaturised Screen‐printed Glucose Biosensors, Using a Water‐based Ink, and the Evaluation of their Electrochemical Behaviour. Issue 8 (25th April 2018) - Hughes, G.; Pemberton, R. M.; Nicholas, P.; Hart, J. P.
Abstract: This paper describes a simple, convenient approach to the fabrication of microband electrodes and microband biosensors based on screen printing technology. These devices were printed in a three‐electrode configuration on one strip; a silver/silver chloride electrode and carbon counter electrode served as reference and counter electrodes respectively. The working electrodes were fabricated by screen‐printing a water‐based carbon ink containing cobalt phthalocyanine for hydrogen peroxide detection. These were converted into a glucose microband biosensor by the addition of glucose oxidase into the carbon ink. In this paper, we discuss the fabrication and application of glucose microband electrodes for the determination of glucose in cell media. The dimensions (100–400 microns) of the microband electrodes result in radial diffusion, which results in steady state responses in the absence of stirring. The microband biosensors were investigated in cell media containing different concentrations of glucose using chronoamperometry. The device shows linearity for glucose determination in the range 0.5 mM to 2.5 mM in cell media. The screen‐printed microband biosensor design holds promise as a generic platform for future applications in cell toxicity studies. Abstract :